Role of Di-Tyrosine and Di-Tryptophan in Alpha- and Beta-Casein Cross-Linking Triggered by Riboflavin-Induced Photo Oxidation and Peroxyl Radicals - Aspee-Lamas, A; Barrías-González, P (ELSEVIER SCIENCE INC, 2018)
Sin Resumen Disponible